Two mistletoes are too many? : interspecific occurrence of mistletoes on the same host tree - Arruda, Rafael (2013)
Mistletoe can have a major impact on the fitness of the host plant. If there is more than one species of mistletoe on the same host tree, the overall impact might be amplified. We report the occurrence of more than one species of mistletoe on the same host tree. Although it is not a rule in the field, to our knowledge, there have been no studies of this topic. In most cases, two species of mistletoe were recorded on the same host tree, although we recorded three species of mistletoe on one occasion. This demonstrates that different species of mistletoe can be compatible with the same host species. Therefore, compatibility (structural and physiological) might be an important factor for the occurrence of mistletoe. Recent studies have shown that if the mistletoe does not "recognize" the host species, the deposited seeds will germinate but the haustorium will not penetrate the host branch. This is probably the primary mechanism in the establishment of more than one species of mistletoe on the same host, which can trigger a cascade of harmful effects for the host species.